Design of buildings through Linear Time-History Analysis optimising ground motion selection: A case study for RC-MRFs. (1st August 2019) - Lombardi, Luca; De Luca, Flavia; Macdonald, John
Highlights: EC8-compliant framework for Linear Time-History Analysis as seismic design method. Design of 12-storey archetype accounting for critical design aspects, e.g., staircase. Comparison of input selection for Linear Time-History design through FEMA P1050 and Eurocode 8. Novel index for EC8 input selection for design using Linear Time-History Analysis. Abstract: A novel framework for Eurocode 8-compliant design using Linear Time-History Analysis (LTHA) is discussed. LTHA overcomes the approximations typical of other linear seismic analyses but it still lacks a suitable approach for seismic input selection compatible with Eurocode 8-prescriptions. The critical aspect is to find a balanced compromise to control seismic input variability, suiting design purposes, but still being able to capture specific response features such as pulse-like effects. A LTHA design procedure has been included in ASCE/SEI 7-16 (2017) and described in FEMA P-1050 (2015), suggesting spectral-matching of three ground motions as input, so that LTHA can be used as alternative to Response Spectrum Analysis (RSA). Herein, a 12-storey regular Reinforced-Concrete Moment-Resisting-Frame building is employed as case-study. Different ground motion selection strategies are compared. Firstly, three suites of spectrum-compatible ground motions are used referring to requirements of Eurocode 8 for nonlinear time-history analysis and compared with LTHA-ground motion selection procedure included in FEMA P-1050. A new index for LTHA ground motion selection ( Ieq ) is proposed to control response variability in relation to the dynamic properties of the structure aimed at obtaining a suitable input for LTHA design. A target value for Ieq is proposed on the basis of structural response for far-field and near-field suites and an ad hoc suite of pulse-like ground motions selected considering pulse periods lower than the fundamental period of the structure. The difference in terms of design results between LTHA and RSA is employed as benchmark to evaluate the suitability of Ieq for LTHA design.